Improved Bathymetric Dataset and Tidal Model for the Northern Bay of Bengal. Issue 6 (1st November 2016) - Krien, Y.; Mayet, C.; Testut, L.; Durand, F.; Tazkia, A. R.; Islam, A. K. M. S.; Gopalakrishna, V. V.; Becker, M.; Calmant, S.; Shum, C. K.; Khan, Z. H.; Papa, F.; et al.
ABSTRACT: The Bengal Delta is a highly complex and vulnerable environment where key dynamical features such as tides, storm surges, salinity, and sediment transport strongly depend on the accurate bottom topography representation. To curb the lack of accuracy of widely used global bathymetry databases in this shallow region, we produced an improved coastal bathymetry for the Bengal Delta through an exhaustive and thorough compilation of 70 nautical charts and river surveys. We merged this bathymetry dataset with a high-resolution digital evaluation model, resulting in a novel, consistent product with unprecedented coverage, from the deep parts of the ocean basin (north of 20°N) to the far upstream areas of the delta (around 24°N). This new bathymetry reduces errors in the tidal residuals by a factor of 2–3 for most coastal gauges as compared to global tidal models. The best results are obtained for the Hooghly River, where errors are as low as 6 cm. The improvement in the mouth of the Meghna is moderate, suggesting the possible rapid evolution of the bathymetry due to strong sediment transport. This new bathymetry is expected to significantly improve the modeling of coastal processes such as storm surges in the northern Bay of Bengal.